2013
DOI: 10.1016/j.jpha.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and validation of a fast RP–HPLC method for the determination of dobutamine in rat plasma: Pharmacokinetic studies in healthy rat subjects

Abstract: A novel isocratic reverse phase high performance liquid chromatography (RP–HPLC) with photo diode array (PDA) detection method for the determination of dobutamine (DBT) in rat plasma was developed and validated after optimization of various chromatographic conditions and other experimental parameters. Homoveratrylamine was used as an internal standard. Methanol was used as the extracting solvent for the preparation of plasma samples. Samples were separated on a Symmetry C18 (250 mm×4.6 mm i.d., 5 μm) analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…10,11,19,20,78–82 Also, the TU-SAMs sensor exhibits low DLs for DB, PA, AM, and DAC determination compared to other reported methods in the literature, Table S2 (ESI†). 8,9,29,30,35,36,43,44…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11,19,20,78–82 Also, the TU-SAMs sensor exhibits low DLs for DB, PA, AM, and DAC determination compared to other reported methods in the literature, Table S2 (ESI†). 8,9,29,30,35,36,43,44…”
Section: Resultsmentioning
confidence: 99%
“…10,11,19,20,[78][79][80][81][82] Also, the TU-SAMs sensor exhibits low DLs for DB, PA, AM, and DAC determination compared to other reported methods in the literature, Table S2 (ESI †). 8,9,29,30,35,36,43,44 Thus, the synergistic effect between all the modifiers of the composite; CNTs, Au nano and TU, enhances the kinetic process for electro-oxidation of the studied drugs.…”
Section: Effect Of Solution Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation of the percentage differentiation parameter of ≤20% revealed that the developed analytical method acquired a LLOQ of 25 ng/mL, which is comparable with the values in earlier investigations at a concentration of 50 ng/mL [ 46 ]. Therefore, the proposed bioanalytic approach can determine analyte concentrations in plasma with accuracy and precision at the LLOQ [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…MCO was subjected to phytochemical investigation for the detection of the presence of various phytochemicals by using standard methods. [13] Formulation of hydrogel of MCO…”
Section: Preliminary Phytochemical Investigationmentioning
confidence: 99%